Suppression of Fas expression in the hypertensive placental histology of rats given Nano herbal of Rhodomyrtus tomentosa leaves: DOI: 10.48129/kjs.16833 - Situmorang, Putri Cahaya; Syahputra, Rony Abdi; Simanullang, Rostime Hermayerni (Kuwait Journal of Science, 2022)
High blood pressure during pregnancy can signal a high-risk pregnancy and result in difficulties. The expression of Fas is critical for maintaining hypertensive immunity. Fas is prevalent in the trophoblast, which enhances maternal-derived apoptosis. Because it contains acylphloroglucinol, flavonoids, tannins, and triterpenes, Rhodomyrtus tomentosa (haramonting) is commonly used in traditional Indonesian medicine to treat high blood pressure. The goal was to determine and investigate the role of haramonting in lowering Fas expression in hypertensive rats' placental histopathology. The rats were confirmed to be pregnant were divided into five treatments: (a) normal pregnant rats (control), (b) hypertensive rats (c) hypertensive rats + 100mg/KgBW NRT, (d) hypertensive rats + 200mg/KgBW NRT, and (e) hypertensive rats + 400mg/KgBW NRT. On gestation day 20, pregnant rats were euthanized under ketamine anaesthesia. ELISA was used to examine the expression of the HSP family. Immunohistochemistry was used to assess Fas expression. In hypertensive rats, NRT can lower systolic and diastolic blood pressure (P<0.01), and haramonting can improve placental efficiency and restore birth weight. In hypertensive rats, the higher the dose of NRT, the higher the levels of HSP27, HSP70, and HSP90. In placental histology, NRT suppresses Fas expression as anti-apoptotic in trophoblast cells. Because NRT is high in antioxidants and protects cells from hypoxia and dehydration, it suppresses Fas activity in the labyrinthine zone, basal zone, and Yolk Sac.